PENGARUH PERSEPSI HARGA, LOKASI, CITRA MEREK DAN SERTIFIKASI HALAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK HALAL RESTORAN CEPAT SAJI MILIK LUAR NEGERI - Safira, Nurul Aulia; Amalia, Alvien Nur (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to discuss what influences influence purchasing decisions on halal products of foreign-owned fast food restaurants. The independent variables obtained from the preliminary survey results are Price Perception, Location, Brand Image and Halal Certification. While the dependent variable obtained is the purchase decision. Methods of data analysis using Variance Based Structural Equation Modeling Partial Least Square (PLS). The population is residents living in South Jakarta, with a sample of 200 respondents. The sampling technique uses convenience sampling. By using a quantitative descriptive approach. The results of this study indicate that Price Perception has a significant positive effect on purchasing decisions, Location has a significant positive effect on purchasing decisions, Brand Image has a significant positive effect on purchasing decisions and Halal Certification has a significant positive effect on purchasing decisions.